2005
DOI: 10.1007/11528043_24
|View full text |Cite
|
Sign up to set email alerts
|

Grounding Collaborative Knowledge Building in Semantics-Based Critiquing

Abstract: Abstract. In this paper we investigate the use of Latent Semantic Analysis (LSA), Critiquing Systems, and Knowledge Building to support computerbased teaching of English composition. We have built and tested an English Composition Critiquing System that make use of LSA to analyze student essays and compute feedback by comparing their essays with teacher's model essays. LSA values are input to a critiquing component to provide a user interface for the students. A software agent can also use the critic feedback … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Early studies of EssayCritic (Mørch et al, 2005) showed its usefulness as a tool facilitating writing in English and supplementing teachers' feedback. However, a study in Hong Kong found no significant difference between the grades achieved by students who used EssayCritic and those who revised their texts themselves (Lee, et al, 2009).…”
Section: Facilitating the Writing Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies of EssayCritic (Mørch et al, 2005) showed its usefulness as a tool facilitating writing in English and supplementing teachers' feedback. However, a study in Hong Kong found no significant difference between the grades achieved by students who used EssayCritic and those who revised their texts themselves (Lee, et al, 2009).…”
Section: Facilitating the Writing Processmentioning
confidence: 99%
“…While digital technologies open up opportunities for enhancing the development of students' writing skills in English (Lee, 2007;Mørch et al, 2005), knowing how to facilitate students' learning with technology and promote AfL skills is a key challenge for teachers.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies of EssayCritic (Mørch et al, 2005) showed that it is a useful tool to facilitate writing in English, as it supplements teachers' feedback. A study in Hong Kong found no significant difference between the grades achieved by students who used EssayCritic and those who revised their texts themselves (Lee, et al, 2009).…”
Section: Feedback In the Writing Processmentioning
confidence: 99%
“…Feedback has been employed in formative assessment to promote the development of students' writing skills (Black & Wiliam, 2009;Hattie, 1999) and AfL has been defined as a classroom practice that involves dialogue and feedback loops between teachers and peers during subject specific problem solving (Gamlem & Munthe, 2014). New digital technologies open up opportunities by providing automated feedback (Dikli, 2006;Kukich, 2000;Sireci & Rizavi, 2000) and specifically for enhancing the development of students' writing skills in English (Lee, 2007;Mørch et al, 2005;Winerip, 2012).…”
Section: Introductionmentioning
confidence: 99%